Normal School and tests in Colombia (2014)
In 1937, the Institute of Experimental Psychology, led by Leo Walther, began the psycho-technical application of tests, based on files and papers and on the social history of the institutions method which supports that in Colombia as well as in Latin America, Psychology arises from the pedagogy context. The basic interest of those psychological studies carried on in education is related, in a special way, to the diagnosis and selection of students from measurement and evaluation. That was the reason to apply the first IQ tests, such as Lewis Terman and Army’s. Furthermore, Dearborn Tests provide the fundamental frameworks to understand and deal with reading difficulties. Ballard hearing tests were also applied. At that time the first manuals on test application by Alejandro Cano, among others, and the normal school students’ first thesis about this subject appeared.